2017
DOI: 10.1371/journal.pone.0180459
|View full text |Cite
|
Sign up to set email alerts
|

Hello handsome! Male's facial attractiveness gives rise to female's fairness bias in Ultimatum Game scenarios—An ERP study

Abstract: The current study delineated how male proposers’ facial attractiveness affect female responders’ fairness considerations and their subsequent decision outcome during the Ultimatum Game (UG). Event Related Potentials (ERPs) were recorded from 17 female subjects, who played the role as responders and had to decide whether to accept offers from either attractive or unattractive male proposers. Behavioral data (Acceptance Ratio and Response time) revealed that, more offers were accepted from attractive-face condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
43
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 79 publications
8
43
1
1
Order By: Relevance
“…The LPP amplitudes induced by real faces were significantly larger than those induced by cartoon faces. This finding is consistent with those of previous studies [7, 10, 49]. When the neutral expressions of real faces and puppet faces were compared, no differences in N170 were observed.…”
Section: Discussionsupporting
confidence: 93%
“…The LPP amplitudes induced by real faces were significantly larger than those induced by cartoon faces. This finding is consistent with those of previous studies [7, 10, 49]. When the neutral expressions of real faces and puppet faces were compared, no differences in N170 were observed.…”
Section: Discussionsupporting
confidence: 93%
“…Compared with simplified cartoon faces, real faces convey more personal information and social meaning. LPP is related to facial attractiveness (Ma et al, 2017;Marzi & Viggiano, 2010;Werheid, Schacht & Sommer, 2007). Therefore, the results of the present study might suggest that real faces are more attractive than simplified cartoon faces to adults.…”
Section: Processing Differences Between Cartoon and Real Facesmentioning
confidence: 56%
“…When the neutral expressions of real faces and puppet faces were compared, no differences in N170 were observed. However, a stronger LPP was found with regard to real faces starting at 400 ms (Ma, Qian, Hu & Wang, 2017). This effect is because of the significance and uniqueness of the real face as well as the understanding of the portrayed individual (Wheatley, Weinberg, Looser, Moran & Hajcak, 2011) because computer-generated faces are usually more difficult to remember (Balas & Pacella, 2015;Crookes et al, 2015).…”
Section: Processing Differences Between Cartoon and Real Facesmentioning
confidence: 99%
“…Jin, Fan, Dai and Ma (2017) found the beauty premium present in online peer-to-peer lending, with lenders tending to be more tolerant towards attractive borrowers' dishonest behaviour. Similarly, Ma, Qian, Hu and Wang (2017) demonstrated that attractive male proposers playing the ultimatum game benefit from favourable bias because of their attractiveness, as a result of compromises to the fairness considerations of the female responders.…”
Section: Beauty and The Beauty Premiummentioning
confidence: 99%